Efeitos do fator XIII da coagulação e da desmopressina no choque hemorrágico não controlado em coelhos - Paulo Roberto Lima Carreiro (2014)
INTRODUCTION: Trauma associated coagulopathy is a primary event after injury. Approximately 30% of severely bleeding patients present to the hospital with some degree of coagulopathy. Hemorrhagic shock management mandates rapid hemorrhage control, adequate organ perfusion, and reversal of coagulopathy. In the present study, we set forth to investigate the hemostatic effect of supplementary factor XIII (FXIII) used alone and in conjunction with permissive hypotension (PH) and or Desmopressin (DDAVP), after uncontrolled bleeding. METHODS: Fifty four (n=54) New Zealand rabbits were randomized in 9 groups (n=6 per group) as follows: Group 1 (GS): Sham; Group 2: FXIII and normotensive fluid resuscitation (NFR); Group 3: FXIII and PH; Group 4: FXIII/DDAVP/NFR; Group 5: FXIII/DDAVP/PH; Group 6: NFR only; Group 7: FXIII w/o hemorrhage; Group 8: FXIII/DDAVP w/o hemor-rhage; Group 9: PH only. Blood samples were obtained at baseline and at the end of the exper-iment for thromboelastometry (ROTEM®). Intra-abdominal blood loss was assessed at the end of the experiment. Data were analyzed as percent variation of medians compared to baseline values using the Mann-Whitney test. Statistical significance was set at p<0.05. RESULTS: CT (clot time): Decrease in CT translates into more rapid clotting. Animals in G8 clotted faster than G1 (Final CT -46.9% X -6.7%, p=0.045); on the same token, G2 clotted faster than G6 (-48.6% X 1.9%, p=0.008). In addition, G5 and G3 compared to G6 (-43. 9% X 1.9%, p=0.013) and (-29.2% X 1.9%, p=0.045), respectively. Alfa angle: Increased alpha angle translates into more fibrin production. Groups 3, 4, 5 and 9 all increased alpha angle compared to G6: (12.3% X -8.5%, p= 0.045); (29.2% X -8.5%, p=0,031); (20.3% X -8.5%, p=0.02); (13.2% X -8.5%, p=0.031), respectively. MAXVT (Maximum velocity time): Negative variation means less time to maximum velocity. G8 performed better than G1 (-49.2% X -10%, p=0.02). Groups 2 and 5 performed better than G6; (-52.2% X -11.8%, p=0.013); (-49.6% X -11.8%, p=0.031), respec-tively. AUC (Area under the curve): Greater area correlates with better clotting. G5 was better than G2 with respect to the AUC (-9.3% X -21.7%, p=0.045). Interestingly, there were no sta-tistically significant differences with respect to the maximum clot firmness (MCF). Intra-ab-dominal blood loss was significantly less in groups 5 and 9 compared to groups 2 and 6. CON-CLUSION: NFR fluid strategy impairs adequate coagulation compared to PH. That is partially reversed by supplementary FXIII and DDAVP. Furthermore, DDAVP potentiates the effect of FXIII. PH reduces bleeding even without FXIII or DDAVP administration.